Integrasi Pendekatan Acuan Patokan (PAP) dan Pendekatan Acuan Normatif (PAN) dalam Konteks Penilaian Pembelajaran Sekolah - Ikhlasul Amal (Dinas Pendidikan, Pemuda dan Olahraga Daerah Istimewa Yogyakarta, 2024)
An approach that is often used to assess an educator is needed in order to match what is expected. It is expected that with a good understanding of the concept of assessment, teachers will be able to adjust and evaluate students' skills according to their actual needs. The purpose of this study was to assess the effectiveness of integrating the Benchmark Assessment (PAP) and Normative Reference Approach (PAN) in teaching. The research method used was a descriptive qualitative approach using a case study at Warungboto State Elementary School, Umbulharjo District, Yogyakarta. The data collection method used in this research was observation, interview and documentation study. The data analysis method used in the research is descriptive analysis technique. The research results show that: 1). There is still a lack of understanding regarding the integration paradigm of the Benchmark Reference Assessment (PAP) and the Normative Reference Approach (PAN). The implementation of assessments using the Benchmark Reference Approach (PAP) and Normative Reference Approach (PAN) has not been carried out thoroughly, openly, honestly and comprehensively, so teachers still need a holistic approach that involves developing teacher professionalism, collaboration between fellow teachers, updating the use of technology, adjustments curriculum, development of effective assessment tools and implementation of continuous feedback and reflection. 2). There is still a need for further training for teachers, as well as addressing teacher problems such as workload and assessment pressure.